Analisis Pengaruh Promosi dan Harga terhadap Minat Beli Konsumen di Minimarket Gading Mas - Muid, Wilson; Risdwiyanto, Andriya (Universitas Proklamasi 45, 2025)
This study aims to determine the effect of promotions and prices on consumer purchasing interest in Gading Mas Minimarket. The sample in this study amounted to 74 people, using accidental sampling technique, which is a technique for determining samples by chance. The method of data collection in this study is by giving questionnaires to customers at Gading Mas Minimarket. This study uses a descriptive analysis method through quantitative analysis and measurement of the variables studied using a Likert scale using SPSS (Statistical Program for Social Science) version 20 statistical software. The results of the analysis show that promotion and price variables (independent variables) have a significant effect on purchasing interest (dependent variable), both partially and simultaneously.